Fusion: coalesced confidential storage and communication framework for the IoT. Issue 15 (30th April 2015) - Bagci, Ibrahim Ethem; Raza, Shahid; Roedig, Utz; Voigt, Thiemo
Abstract: Comprehensive security mechanisms are required for a successful implementation of the Internet of Things (IoT). Existing solutions focus mainly on securing the communication links between Internet hosts and IoT devices. However, as most IoT devices nowadays provide vast amounts of flash storage space, it is as well required to consider storage security within a comprehensive security framework. Instead of developing independent security solutions for storage and communication, we propose Fusion, a framework that provides coalesced confidential storage and communication. Fusion uses existing secure communication protocols for the IoT such as Internet protocol security (IPsec) and datagram transport layer security (DTLS) and re‐uses the defined communication security mechanisms within the storage component. Thus, trusted mechanisms developed for communication security are extended into the storage space. Notably, this mechanism allows us to transmit requested data directly from the file system without decrypting read data blocks and then re‐encrypting these for transmission. Thus, Fusion provides benefits in terms of processing speed and energy efficiency, which are important aspects for resource‐constrained IoT devices. This paper describes the Fusion architecture and its instantiation for IPsec‐based and DTLS‐based systems. We describe Fusion's implementation and evaluate its storage overheads, communication performance, and energy consumption. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Fusion uses existing secure communication protocols for the Internet of Things (IoT) such as Internet protocol security (IPsec) and datagram transport layer security (DTLS) and re‐uses the defined communication security mechanisms within the storage component. Thus, trusted mechanisms developed for communication security are extended into the storage space. Notably, this mechanism allows us to transmit requested data directly from the file system without decrypting read data blocks and then re‐encrypting these for transmission.